Konstruksi Greedy Kode Lexicographic untuk Membangun Perluasan Kode Golay (24 12,8) - Aini, Aurora Nur; Irawanto, Bambang (JURNAL SAINS DAN MATEMATIKA, 2011)
Golay codes can be constructed by lexicographic codes. Lexicographic codes constructed by Greedy algorithm. Greedy construction is one type of Greedy algorithm. Given codes with minimum distance d and length n. To construct the greedy algorithm, the codeword with length n are processed in some fixed order, and the next codeword is inserted in the code when its distance from all codewords previously selected is d. On Greedy construction, to set (n, k,d) codes, we only need to set (n-k,k) codes with k iteration. Keywords: linear codes, lexicographic codes, Golay, generator matrix